Experimental studies on creep running at high temperatures over days and weeks - Teraud, W V (Journal of physics. Conference series, 2018)
Experimental studies are helpful for both verifying existing theoretical predictions and finding new phenomena. Conducting long-term high-temperature experiments is subject to a number of difficulties. These difficulties are considered when conducting high-temperature tests for creep and long-term strength.. The paper presents solutions to the most typical problems arising during the set-up and running of long-term tests. The problems of stabilization of the temperature in the furnace, measurement of the parameters of the heated specimen and fire safety are considered.